Model Development of Sustainable Island Ecotourism in Seribu Islands Regency: NRBV, ISM, and DEMATEL Approaches - Untung Setiyo Purwanto; Aryo Sahid Sujiwo (Institut Manajemen Wiyata Indonesia, 2026)
Island ecotourism plays a crucial role in achieving sustainable development goals; however, its development is inherently complex. This study aimed to identify key elements of island ecotourism based on the Natural Resource-Based View (NRBV), analyze the interrelationships among these elements, determine their hierarchical structure, and classify them into relevant categories. Data were collected through a survey involving 12 expert respondents and 64 visitors. The study was conducted on Tidung Island and Untung Jawa Island in the Seribu Islands Regency, Jakarta Province, between August and October 2024. The data were analyzed using the Delphi method, MICMAC, ISM, and DEMATEL approaches. The findings identified key elements of island ecotourism with strong influence on sustainable development. These included unique local resources, effective green marketing, supportive and consistent government policies, adequate facilities and infrastructure, high-quality products and services, and the promotion of environmental awareness and appreciation. The results indicate that these elements collectively play a critical role in shaping sustainable island ecotourism development. These findings provide a strategic framework for stakeholders and policymakers in formulating development strategies. In particular, emphasis should be placed on strengthening unique local resources, green marketing practices, and consistent government policy support to ensure the long-term sustainability of island ecotourism.